RELEVANSI KURIKULUM DAN WUJUD KONGKRET TUJUAN PEMBELAJARAN BAHASA ARAB - Novita Rahmi (Institut Agama Islam Negeri (IAIN) Metro, 2017)
Learning is a conscious effort to achieve specific goals. Meanwhile, the curriculum is a tool to achieve the desired educational goals. Manifestations of the curriculum in a learning activity consists of several components that work together to achieve educational goals. Besides the curriculum should serve as guidance in organizing educational activities carried out in schools. The curriculum also regulate matters relating to the type of program, for the organization, strategy implementation, the responsible, infrastructure, and others. Thus, the curriculum is closely linked to the learning objectives. Likewise with Arabic learning, curriculum developed useful as possible to realize the goal of learning Arabic. All the elements related to the curriculum as an educational tool, children of students, the situation of education and learning activities work together to achieve the desired goal. The curriculum is a means to achieve educational goals.